(untitled) - Latif, Samsar Kamar bin Hj. Ab. (Kuala Lumpur, 2003)
There is a great need for suitable law textbooks which can be used by students who are studying Malaysian partnership law in the universities and colleges in Malaysia.
Keywords: Partnership,Hiệp hội; Malaysia,Malaysia